YAP1::KMT2A fusion-positive sarcoma: An emerging soft tissue tumor entity with morphological features resembling a sclerosing epithelioid fibrosarcoma - Ayush Agarwal; Bharat Rekhi; Vineeta Goel; Jyoti Bajpai; Sameer Rastogi (Indian Journal of Pathology and Microbiology)
Sclerosing epithelioid fibrosarcoma (SEF) and low-grade fibromyxoid sarcoma (LGFMS) constitute a morphological continuum with certain overlapping histopathological features and MUC 4 immunopositivity. SEF is characterized by EWSR1 gene rearrangement, is relatively more aggressive and shows a limited response to chemotherapy. Lately, a subset of tumors with morphological features of SEF, but lacking MUC4 immunostaining and EWSR1 gene rearrangement have been observed. We report the first case of YAP1::KMT2A-positive sarcoma from the Indian subcontinent along with a review of similar tumors reported previously. A case of 31-year-old male presented with a 3 cm painful lump in the right suboccipital region. Histopathological examination of the excised specimen revealed a cellular tumor composed of atypical spindle and epithelioid cells, exhibiting moderate nuclear pleomorphism, arranged in cords, embedded in a dense collagenous/hyalinized stroma. By immunohistochemistry, the tumor cells were diffusely positive for cyclin D1 and negative for MUC4, desmin, myogenin, β-catenin, STAT6, myoD1, SMA, and S100P. By fluorescence in-situ hybridization, EWSR1 gene rearrangement was negative. Next-generation sequencing (NGS) revealed YAP1exon5::KMT2Aexon4 fusion. Given a positive resection margin, he underwent a revision surgery involving wide local excision of the lesion including the outer table of the occipital bone followed by image-guided radiation therapy. Over 2 years of his follow-up, the patient is alive with no evidence of recurrence. Thus, YAP1::KMT2A positive sarcomas have distinct molecular and overlapping histopathological features with SEF, with relatively less aggressive disease course. Documentation of additional similar tumors with long-term follow-up is required.